Inovasi Pelayanan Publik Berbasis Aplikasi di Kantor Imigrasi Kelas I TPI Palembang - Pakpahan, Muhammad Prawira; Pangga, Kiki Kurnia (Universitas Batanghari Jambi, 2025)
This research aims to find out how the M-Passport application is implemented and the factors inhibiting the M-Passport application. This research focuses on the implementation of the M-Passport application, which has basically been implemented well, but there are still people who do not know about the M-Passport application due to socialization that has not reached all community networks. The approach used in this research refers to Rogers' (1995) innovation theory which has 5 (five) dimensions, namely relative advantages, compatibility, complexity, trainability, observability. Data collected through interviews, documentation and observation and analyzed qualitatively. The research results show that 1) the relative advantages dimension has a profitable novelty value; 2) the compatibility dimension is compatible with the innovation being replaced and adapts to existing needs; 3) the complexity dimension seems more difficult because there are additional features and processes; 4) the trainability dimensions of the M-Passport application have been tested with good results before being implemented; and 5) the observability dimension is easy to observe and communicate because the M-Paspor application was created to be clear, concise and concise.